The profiles of free, esterified and insoluble-bound phenolics in peach juice after high pressure homogenization and evaluation of their antioxidant capacities, cytoprotective effect, and inhibitory effects on α-glucosidase and dipeptidyl peptidase-Ⅳ - Shenke Bie; Shuai Zhao; Shengbao Cai; Junjie Yi; Linyan Zhou (Food Chemistry: X, 2024)
The phenolic profiles, antioxidant capacities, cytoprotective effect, and α-glucosidase and DPP-IV inhibitory capacity of free (FP), esterified (EP) and insoluble-bound (IBP) phenolic fractions in ‘Lijiang snow’ peach juice after high pressure homogenization (HPH) were investigated, and the molecular docking was used to explore the enzyme inhibition mechanism. HPH increased total phenolic and total flavonoid contents in three fractions without changing compositions. The IC50 of radicals scavenged by three fractions were all reduced by HPH. The best inhibition on intracellular ROS production were found for phenolic fractions after HPH at 300 MPa, with ROS levels ranged within 95.26–119.16 %. HPH at 300 MPa reduced the apoptosis rates of FP and EP by 16.52 % and 9.33 %, respectively. All phenolic fractions showed effective inhibition on α-glucosidase and DPP-IV by formation of hydrogen bonding and van der Waals forces. This study explored the feasibility of HPH to enhance the phenolics and bioactivity of peach juice.